2005
DOI: 10.1002/cbic.200500082
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoazurin–Nitrite Reductase Interactions

Abstract: The nitrite reductase-binding site on pseudoazurin has been determined by using NMR chemical-shift perturbations. It comprises residues in the hydrophobic patch surrounding the exposed copper ligand His81 as well as several positively charged residues. The binding site is similar for both redox states of pseudoazurin, despite differences in the binding mode. The results suggest that pseudoazurin binds in a well-defined orientation. Docking simulations provide a putative structure of the complex with a binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 25 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…In pseudoazurins from denitrifying bacteria, this region of the surface provides a recognition site for its CuNIR electron-transfer partner [3,14]. Structural investigations have shown that following the formation of the encounter complex, via interactions between complementary surfaces on the two proteins, the redox centres of pseudoazurin and the CuNIR are positioned in close proximity, promoting fast electron transfer [15]. The close functional relationship between the pseudoazurin and CuNIR is also reflected in the fact that the genes encoding the CuNIR and the pseudoazurin are normally found together as part of the same operon.…”
Section: Introductionmentioning
confidence: 98%
“…In pseudoazurins from denitrifying bacteria, this region of the surface provides a recognition site for its CuNIR electron-transfer partner [3,14]. Structural investigations have shown that following the formation of the encounter complex, via interactions between complementary surfaces on the two proteins, the redox centres of pseudoazurin and the CuNIR are positioned in close proximity, promoting fast electron transfer [15]. The close functional relationship between the pseudoazurin and CuNIR is also reflected in the fact that the genes encoding the CuNIR and the pseudoazurin are normally found together as part of the same operon.…”
Section: Introductionmentioning
confidence: 98%
“…As with all other Cu-NiRs, the protein is a homotrimer with two copper atoms per monomer, ϳ12 Å apart. The type 1 copper site has four ligands (His-126, His-177, Cys-167, and Met-182) and is located a few angstroms beneath a hydrophobic surface (8), which is the docking site for an electron donor protein (10,11). The type 2 copper site is situated at the monomer-monomer interfaces and has ligands from both monomers (His A131, His A166, His B338), forming a propeller-shaped structure with the copper at its center.…”
mentioning
confidence: 99%
“…Previous results show that BiGGER can be a powerful modelling tool when used in this manner, even when the experimental data are only applied after the search stage to score the models produced [11,19,[21][22][23][24][25][26][27]. However, there are two advantages to using the experimental data to constrain the search space.…”
Section: Results and Further Workmentioning
confidence: 91%
“…The value of K can also be an upper bound, or a specific value, or even any number of values). In this case, there are at least two atoms of set A within neighbourhood 3 of atom set B if the displacement lies in ranges [−3,−1] or [2,5] or [7,11]. In range [2,3] all three A atoms are in the neighbourhood 3 of B.…”
Section: Constraining the Search Space To Active Regionsmentioning
confidence: 96%